Pengaruh Disintegran dan Cara Pencampuran Terhadap Sifat Fisika Kimia Telmisartan - Hestiary Ratih; Fikri Alatas; Jessie Sofia Pamudji; Sundani Nurono Soewandhi (Fakultas Farmasi Universitas Pancasila, 2021)
Telmisartan (TMS) has a compact structure and is interlocked between crystal units. As a result, the substance has a high electrostatic force, which causes TMS to sintering when compressed into tablets. One method of overcoming sintering on TMS tablets is to add a disintegrant to the compressed tablet. The disintegrants used are derived from starch groups: Starch 1500® (S1500) and sodium starch glycolate (SSG), as well as microcrystalline cellulose (MCC) and croscarmellose sodium (CCS) groups. The purpose of this study was to examine the effects of several disintegrants on the dissolution and physicochemical properties of TMS with various treatments. TMS was varied with each disintegrant at a ratio of 1:9 % b/b. The treatment of TMS binary mixtures with various disintegrants includes physical mixtures, milled mixtures, compressed mixtures, and crushed compressed mixtures. Characterization and evaluation include PXRD and SEM testing as well as dissolution test. The characterization of PXRD and SEM in various treatments showed the effect of physicochemical properties on the TMS binary mixture with various disintegrants. The combination of TMS:CCS with a ratio of (1:9) resulted in the highest dissolution rate in all treatments.The treatment of the milled mixture produced the highest dissolution with DP60 minutes, which was around 55.86±2.47%. The addition of disintegrants to TMS with various treatments may reduce sintering but is not sufficient to meet the requirements for TMS dissolution, which dissolves within 30 minutes in phosphate buffer medium pH 7.5 with Q>75%.